2013
DOI: 10.1038/onc.2013.495
|View full text |Cite
|
Sign up to set email alerts
|

SALL4, a novel marker for human gastric carcinogenesis and metastasis

Abstract: SALL4, a zinc-finger transcriptional factor for embryonic stem cell self-renewal and pluripotency, has been suggested to be involved in tumorigenesis. The role of SALL4 in human gastric cancer, however, remains largely unknown. In this study, we demonstrated that SALL4 was aberrantly expressed at both mRNA and protein levels in human gastric cancer tissues, and SALL4 level was highly correlated with lymph node metastasis. Enforced expression of SALL4 enhanced the proliferation and migration of human gastric ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
109
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(113 citation statements)
references
References 39 publications
4
109
0
Order By: Relevance
“…The staining of SALL4 was mainly found in the cytoplasm with a diffuse distribution in the nucleus. The result of predominantly cytoplasmic staining of SALL4 was dissimilar with most studies of SALL4 in other carcinomas which observed largely nuclear staining of SALL4 [15,29,30]. Under some circumstances, some kinds of transcription factors may be located in the cytoplasm prior to activation, and become relocated in the nucleus in response to the appropriate signal [31].…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…The staining of SALL4 was mainly found in the cytoplasm with a diffuse distribution in the nucleus. The result of predominantly cytoplasmic staining of SALL4 was dissimilar with most studies of SALL4 in other carcinomas which observed largely nuclear staining of SALL4 [15,29,30]. Under some circumstances, some kinds of transcription factors may be located in the cytoplasm prior to activation, and become relocated in the nucleus in response to the appropriate signal [31].…”
Section: Discussionmentioning
confidence: 50%
“…SALL4, as a specific and sensitive marker, has been proved to be beneficial in screening out metastatic germ cell tumors, especially metastatic yolk sac tumors [11]. SALL4 was demonstrated to play an oncogenic role in gastric cancer by modulating cell stemness and epithelial-mesenchymal transition and supposed to be a new target for diagnosis and therapy for human gastric cancer [15]. The over expression of SALL4 has been observed in human liver cancer [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, down-regulation of SALL4 inhibits liver cancer cell proliferation in vitro as well as in tumor xenograft models. We have recently reported that SALL4-overexpression enhances while knockdown of SALL4 inhibits the proliferation of gastric cancer cells [34]. In consistent with this observation, SALL4 knockdown also inhibits endometrial cancer cell growth in vitro and tumorigenicity in vivo due to the inhibition of cell proliferation and increased apoptosis [35].…”
Section: Sall4 and Cell Proliferation And Apoptosismentioning
confidence: 61%
“…The research from our group has indicated that the SALL4 level is highly correlated with lymph node metastasis of gastric cancer [34]. Enforced expression of SALL4 enhances the migration of human gastric cancer cells, whereas knockdown of SALL4 by siRNA leads to the opposite effects.…”
Section: Sall4 and Invasive Migrationmentioning
confidence: 99%